Financing New Investments under Asymmetric Information: A General Approach - Robin Boadway; Michael Keen (Queen's University, Department of Economics, 2004)
We study the efficiency of credit market equilibria when financial intermediaries cannot observe the riskiness or the returns of potential investment projects. With loan financing, there is over-investment in high-return, high-risk projects and under-investment in low-return, low-risk projects relative to the social optimum. If firms have the choice of equity finance, there is unambiguously over-investment under reasonable conditions. The well-known cases of Stiglitz and Weiss and of de Meza and Webb emerge as special cases. The results are extended to allow for signaling and screening equilibria.
Keywords: G14; G18; 330; Credit Markets; Asymmetric Information